Efektifitas Relaas Melalui Siaran Radio dan Surat Tercatat: (Studi di Mahkamah Syar’iyah Bireuen) - Bardan, Fadhilah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam (IAI) Al-Aziziyah Samalanga, 2024)
The summoning of court hearings and notification of court decisions to litigants has evolved alongside advancements in information and communication technology. This study aims to evaluate the effectiveness of summons delivered via radio for defendants whose whereabouts are unknown (in absentia) and through registered mail in court proceedings, specifically focusing on trials at the court level. The research employs a normative juridical method with a descriptive-analytical approach, supported by secondary and primary data obtained through literature studies and interviews. The problem analysis is conducted qualitatively from a juridical perspective. The findings reveal that summons via radio are no longer effective in handling in absentia cases. Regulatory reforms are needed as this method is outdated and no longer aligns with the information consumption habits of the community. Courts should also conduct public outreach to ensure better awareness. Meanwhile, the implementation of registered mail summons at the Mahkamah Syar’iyah Bireuen, although in compliance with Supreme Court Regulation (PERMA) No. 7 of 2022 through collaboration with PT Pos Indonesia, remains suboptimal due to procedural inefficiencies. This underscores the need for procedural law training, as well as monitoring and evaluation of the partnership with PT Pos Indonesia (Persero) for the use of registered mail services.